(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This study provides a comprehensive examination of speech culture as a fundamental component of human communication and social interaction. The research explores the historical development of speech culture from ancient civilizations to contemporary digital communication, analyzing its theoretical foundations, cultural variations, and evolving significance in modern society. The paper investigates how speech culture reflects societal values, educational practices, and communicative competence across different historical periods and cultural contexts.